The Theatricality of Organizational Atmosphere - Lydia Jørgensen (Ambiances)
In recent years, it has been argued that the public sector should stage citizen experiences to put the human before the system. The paper explores how a public organization stages such citizen experience in practice. In order to do that, the paper builds on Gernot Böhme’s understanding of atmosphere as a scenographic practice, reflecting how aesthetic practices have become pivotal in an ongoing aesthetization process in society as an enhanced focus on experiental value. The paper engages with contemporary theatre to critically elaborate the theatricality of staging organizational atmospheres as both a social and political concern. While the paper studies how the staging of atmospheres can be theoretically understood and empirically investigated, the paper argues that the staging of organizational atmosphere contributes to thinking organization as an aesthetic phenomenon.